Valor nutricional da silagem de Urochloa brizantha cv. Piatã em consórcio com Stylosanthes capitata cv. Campo Grande - Ciudrowski, Rafael (2017)
Brazil presents large areas planted with tropical forages and there is a great challenge to store these forages and make them available during the winter period, keeping them nutritional quality. The objective of this work was to evaluate the nutritional value of silage the Urochloa brizantha cv. Piatã exclusive or in consortium with Stylosanthes capitata cv. Campo Grande. The experiment was conducted in an area belonging to the UTFPR (Universidade Tecnológica Federal do Paraná), located in the municipality of Dois Vizinhos, from January to May 2017 and the laboratory analyzes were performed at the Laboratory of Bromatology of this same institution. A completely randomized experimental design with four treatments and three replicates, the material was silage in PVC microsils, the treatments were 100% of Urochloa brizantha cv. Piatã; 80% of Urochloa brizantha cv. Piatã and 20% Stylosanthes capitata cv. Campo Grande; 60% of Urochloa brizantha cv. Piatã and 40% Stylosanthes capitata cv. Campo Grande; 40% of Urochloa brizantha cv. Piatã and 60% Stylosanthes capitata cv. Campo Grande.The results of the study were as follows: DM, Ash, CP, NDF, ADF, ADL, and CHOS. It was observed that the silage of Urochloa brizantha cv. Piatã intercropped with Stylosanthes capitata cv. Campo Grande allowed for desirable fermentations and increased its nutritional value.